(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The regions play a crucial role in the development of a nation’s economy. Strengthening vertical integration is one of the key prerequisites for achieving balanced economic growth, as each region must develop its productive forces based on its mineral and resource potential. The rational distribution of industrial capacities in line with regional characteristics fosters sustainable economic development. In particular, the expansion of small business and private entrepreneurship, enhancement of export potential, and strengthening of diversification policies ensure the stability and resilience of regional economies.